A memória maçônica da Augusta e respeitável loja simbólica (ARLS) Ordem e Trabalho no cemitério municipal da Vila Jacuí - Restinga Seca/RS - Silva, Jair Flores da (2024)
In this master's thesis in Cultural Heritage from the Postgraduate Program in Cultural Heritage (PPGPC) at the Federal University of Santa Maria (UFSM), we seek to recover at least a significant part of the historical memory of the Masonic Lodge Order and Work that was active in the period from 1895 to 1912, in the current village of Jacuí in the municipality of Restinga Seca, RS. Such research was only possible to carry out thanks to the discovery of this Lodge through the tomb or funerary art still existing in the cemetery of that village. Some tombs containing Masonic symbols that aroused the interest of this researcher, defy time and still arouse the curiosity of visitors. Therefore, our research was developed in a few stages. Initially, we carried out archaeological research with a visit to the site, identifying names seeking to reconstruct the human past linked to tomb art with the symbolic characteristics of Freemasonry. Next, we carried out ethnographic research as we were able to gather a list of the names of the people who made up the membership of the Masonic Lodge Order and Work in that period, their behaviors, their customs and their characteristics within that community in which they were inserted. We carried out documentary research using primary sources, that is, documents issued and received during the Store's existence and which constitute this important collection containing information that was treated analytically. We seek to use these documents with the purpose of contextualizing the most important and significant facts of its members and the Lodge itself in relation to the historical and cultural episodes of that particular moment in history. We also carried out descriptive research as we tried to bring to light some characteristics of the inhabitants of that village when immigrants arrived and the result of this insertion as an exchange of cultures, whose common objectives were economic and social growth and development. Our research went through three stages, namely: Pre-analysis of the collection made available by the Grande Oriente do Rio Grande do Sul and the Masonic Lodge Order and Work. We organized the materials classifying the most important ones for interpreting them, since they are handwritten. And analysis of the information obtained and commented publication. This research will serve to constitute a historical collection for the Masonic Lodge Order and Work and for other researchers interested in the subject.